The Legitimacy of change: adopting/adapting, implementing and sustaining reforms within community corrections agencies - Rudes, Danielle S. (The British journal of criminology, 2021)
Many criminal justice institutions implement evidence-based reforms. While most scholars are aware of implementation challenges, we still know relatively little about sustainability. Using longitudinal data from criminal legal staff implementing an evidence-based reform, this paper considers: What happens during the implementation of an organizational reform that affects continued use of these reforms? Guided by an organizational change framework, findings suggest sustainability aligns with key organizational goals including legitimacy, efficiency and effectiveness. While all sites saw the reformed practices as legitimate enough to initially consider adoption, two sites never adopted, four sites toyed with reform, and two sites continued to use the reform after the study was over. This paper explores sustainability and identifies legitimacy as an important factor that affects the routinization of new practices. Transformation of organizational change initiatives into routine practices should consider efforts to build legitimacy in lieu of primarily rationalizing on the values of efficiency and effectiveness.